School Feeding : Manual for SABER-SF Exercise - World Bank; World Food Programme; Partnership for Child Development (World Bank, Washington, DC, 2017)
SABER–School Feeding (SABER-SF) is a useful approach to assessing the school feeding policy situationand systems in any country to identify the gaps and plan appropriate capacity development plans and/orroad maps with the government and other stakeholders. It helps countries strengthen their national schoolfeeding programs and/or transition to national school feeding programs with solid policies and systemswhen applicable, and assess progress of implementing each indicator. This manual aims to assist users (government institutions, PCD, World Bank, WFP, and otherstakeholders) to understand, plan, and implement the SABER-SF exercise at the country level. It builds upon the experiences from national SABER-SF workshops held during 2014. The SABER-SF exercise should be as inclusive as possible to ensure broad ownership and support for its implementation. SABER consists of a structured questionnaire whose responses are determined based on consultation with representatives from relevant stakeholders. Stakeholder engagement and consensus building are integral parts of the SABER process as described in this manual. The manual contains a brief explanation of SABER-SF in section two, followed by a discussion in section three of the preparation of the SABER-SF exercise and data collection procedures. Section four explains theme thodology and planning process for a SABER-SF workshop, completion of the questionnaire (and the rationale behind each question or set of questions), and how to use each of the SABER-SF tools includingthe Framework Rubrics and the Scoring Rubrics. Section five covers the process of publicizing the SABERSF report, and section six talks about planning for next steps after the SABER-SF exercise. Section 7provides a timeline for implementing the SABER-SF exercise and quality assurance measures. The manual also includes an annex with the SABER-SF questionnaire and the Framework Rubrics. The annex alsodetails ways to contact the SABER team at the World Bank for any questions or comments in addition toa list of additional resources.